Street art in the space of urban environment of Ryazan - S. S. Pravdolubova; V. A. Egorova; A. O. Zubkova; A. D. Sidorova (Vestnik MGSU)
Introduction. The impact of street art on the state of space of the modern city is investigated. The object of the research is the modern urban environment considered in the context of the changing perception of street art by the urban population. The aspects of forming a favourable urban environment from the point of view of urban dweller’s stay in it are considered.Materials and methods. The methodological basis of the research is an analytical review of materials reflecting the interaction between art and the viewer in general, and street subculture and the urban dweller in particular. The focus of this paper is the concept of the functionality of the time-changing urban environment and its human perception. The research methodology is based on the analysis of the urban space of Ryazan through the prism of its perception by the urban population. The empirical base contains materials, including a statistical study of the opinion of the target audience of teachers, staff and students of the Ryazan Institute (branch) of the Moscow Polytechnic University regarding the existence of the social phenomenon of street art, its dynamics and impact on public opinion, an interview reflecting the view of the artist Alexander Sinitsyn on the state of the Street art movement in Ryazan and the authors’ own participation as artists in the social project “The City in Colours”, which took place in the summer of 2022. The concrete fence of the railway tracks in Moskovskaya street was the object of creativity.Results. The main factors influencing the perception of street art by the population are revealed, the data of statistical research of the state of public consciousness is carried out, reflecting aesthetic views, social activity, involvement in the processes of transformation of the urban environment, the dynamics of perception of the visual range contained in street art objects. The authors of the paper determined the average level of awareness of residents about the activities of street artists and various works of street art.Conclusions. Street art is a new direction that is undergoing transformation processes, adapting to new trends in the modern structure of society and people’s consciousness. Modern subculture of street art will be in demand on the territory of urban space, thanks to its informational, propaganda and aesthetic component.